2013
DOI: 10.1002/j.2161-1882.2013.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gatekeeper Training for Suicide Prevention on University Resident Assistants

Abstract: Resident assistants (RAs) can serve as important suicide prevention gatekeepers. The purpose of the study was to determine if training improved RAs’ crisis communications skills and suicide‐related knowledge and to determine if the knowledge elements predicted crisis communications skills. New RAs showed significant improvement in all areas from pretest to posttest, whereas returning RAs showed no significant increase in any of the areas. None of the knowledge areas predicted communications skills for either g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
1
23
0
3
Order By: Relevance
“…Census, 2010). Although they have several roles, RAs are expected to serve as first-responders when acute or chronic mental health problems and academic problems appear in students living in residence halls (Blimling, 2003; Elleven, Allen, & Wircenski, 2001; Sharkin, Plageman, & Mangold, 2003; Taub et al, 2013). The vast majority of undergraduate RAs hold these positions for only one or two academic years.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Census, 2010). Although they have several roles, RAs are expected to serve as first-responders when acute or chronic mental health problems and academic problems appear in students living in residence halls (Blimling, 2003; Elleven, Allen, & Wircenski, 2001; Sharkin, Plageman, & Mangold, 2003; Taub et al, 2013). The vast majority of undergraduate RAs hold these positions for only one or two academic years.…”
mentioning
confidence: 99%
“…Thus, the annual turnover in the RA workforce is substantial, making RA training and supervision an ongoing task in residence life/housing departments. At most campuses, RA training programs devote minimal time to alcohol, drug, and mental health first-aid, including teaching RAs effective referral skills for these problems (Taub & Servaty-Seib, 2011; Taub et al, 2013). Moreover, the first-aid training conducted by departments of residence life/housing is locally devised and not evidence-informed (Owens, 2011; Taub & Servaty-Seib, 2011; Taub et al, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of investigators have demonstrated the benefits of MHL‐based interventions and peer‐to‐peer mental health support among 4‐year university students (Taub et al, 2013; White et al, 2009). White et al (2009) found that university students who participated in a peer‐health education program reported less alcohol consumption as well as increases in weight management behaviors over the first 3 years of college.…”
Section: Mental Distress Among Community College Studentsmentioning
confidence: 99%